O tożsamości, nieostrości i istotach przedmiotów - Engel, Pascal; Nef, Frederic (Filozofia Nauki, 1996)
The authors analyze some kinds of soritical, modal and temporal paradoxes and examine differnt ways of solving them. They reject the assumption that it is the essence of object that may cause paradox due to its vagueness; we shall not abandon classical logic as well. The explanations and solutions for paradoxes can be found in vagueness of modal logic rather or in usual (and vague) way we use our language.